Legal Pluralism in Traditional Societies: A Case of Agricultural Marketing Relations in Northwest Pakistan - Jan, Inayatullah; Akram, Waqar (The Journal of Humanities & Social Sciences, 2022)
One of the characteristics of traditional village system in the developing countries is the existence of plural legal systems governing social, economic, and political life of the populations. One such example is the prevalence of formal and informal marketing relations in traditional village system in northwest Pakistan. Changes in marketing structures overtime have led to transform the balance between prevailing formal and informal marketing relations. This paper analyzes the marketing relations in northwest Pakistan and changes in this relationship over time. The findings of the paper reveal that two types of regulative mechanisms co-exist in the area that govern the agricultural marketing system: the societal regulative mechanism and the commercialized regulative mechanism. The former is governed by the informal and personalized relations and the latter by new formal and commercialized relations. Due to the rapid influences of modernization and urbanization in the recent past, a shift has taken place from personalized relations to the specialized functional relationships. Despite a tremendous expansion in the new relations, however, farmers‟ switch-over rate is slow because of the functional efficiency of the new system having comparative advantages for the elite groups (progressive farmers) only. To hamper the expansion of potential social polarization in the wake of this imbalanced effect, the large groups of small farmers adhere to the traditional informal relations. Hence, the personalized marketing relations are still efficiently functional and have strong influences on the organization of farm-household relations. The paper concludes that in order to achieve rural institutional sustainability, a balance should be maintained in both personalized and commercialized networks of relations.